Responsabilidad sancionadora de personas jurídicas, entes sin personalidad y administradores - Rebollo Puig, Manuel (Pontificia Universidad Católica del Perú, 2016)
The disciplinary liability of legal entities, which the regulation normally accepts, is not an exception to the principles of existing guilty and of personalizing the sanction: it is a liability for action and fault of the legal entity. In particular, it analyzes the liability of legal entities by the actions of their administrators. And, also, it studies the cases in which the Law provides certain complements or qualifications to that liability. Above all, the cases in which the disciplinary liability of the administrators is evident. It also addresses the liability of entities without personality and it highlights the advantages and difficulties that their application entails.

La responsabilidad sancionadora de las personas jurídicas, que acepta con normalidad el ordenamiento, no es una excepción a los principios de culpabilidad y de personalidad de las sanciones: se trata de una responsabilidad por acción y culpa propias de la persona jurídica. En especial, se analiza la responsabilidad de las personas jurídicas por la actuación de sus administradores. Y, asimismo, se estudian los supuestos en que el Derecho prevé ciertos complementos o matizaciones a esa responsabilidad. Sobre todo, los casos en los que se consagra laresponsabilidad sancionadora de los propios administradores. Se aborda también la responsabilidad de entes sin personalidad y se ponen de relieve las ventajas y dificultades que su aplicación entraña.
Disciplinary Liability of legal entities, entities without personality and administrators
Keywords: Disciplinary Administrative Law; Responsible Entities; Legal Entities; Entities Without Personality; Administrators Of Legal Entities; Derecho Administrativo Sancionador; Sujetos Responsables; Personas Jurídicas; Entes Sin Personalidad; Administradores de Personas Jurídicas; https://purl.org/pe-repo/ocde/ford#5.05.00